Mutual irrigation company monitoring of main canal nitrogen levels: a case study on the role of mutual irrigation companies in water quality management - Wilkins-Wells, John, author; Freeman, David M., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1992)
This paper presents the results of a focused social survey and weekly water quality sampling conducted during the irrigation seasons of 1991 and 1992 in a mutual irrigation company service area. The company is located in northeastern Colorado. The research had two principal objectives. the first was to provide baseline data on nitrates in irrigation company canal water in the upper portion of the Cache La Poudre River Basin, a major irrigated area in Colorado. The second goal was to assess the potential of such companies to initiate pro-active water quality management programs that would address practical needs of shareholder-growers, while at the same time addressing overall State water quality mandates impacting the local river basin.
December 1992.
Keywords: Irrigation water -- Quality -- Colorado -- Cache la Poudre River Watershed; Water quality management; Irrigation -- Colorado -- Management; Nitrogen fertilizers -- Environmental aspects; Environmental monitoring; Nitrogen in agriculture